Research hotspots and trends on spinal cord stimulation for pain treatment: a two-decade bibliometric analysis - Yang, Sheng; Zhong, Sen; Fan, Yunshan; Zhu, Yanjie; Xu, Ningze; Liao, Yue; Fan, Guoxin; Liao, Xiang; He, Shisheng (Frontiers in Neuroscience, 2023)
Background Chronic pain poses a significant social burden. Spinal cord stimulation (SCS) is considered to be the most promising treatment for refractory pain. The aim of this study was to summarize the current research hotspots on SCS for pain treatment during the past two decades and to predict the future research trends by bibliometric analysis. Methods The literature over the last two decades (2002-2022) which was related to SCS in pain treatment was obtained from the Web of Science Core Collection. Bibliometric analyses were conducted based on the following aspects: (1) Annual publication and citation trends; (2) Annual publication changes of different publication types; (3) Publications and citations/co-citations of different country/institution/journal/author; (4) Citations/co-citation and citation burst analysis of different literature; and (5) Co-occurrence, cluster, thematic map, trend topics, and citation burst analysis of different keywords. (6) Comparison between the USA and Europe. All analyses were performed on CiteSpace, VOSviewer, and R bibliometrix package. Results A total of 1392 articles were included in this study, with an increasing number of publications and citations year by year. The most highly published type of literature was clinical trial. USA was the country with the most publications and citations; Johns Hopkins University was the institution with the most publications; NEUROMODULATION published the most papers; the most published author was Linderoth B; and the most cited paper was published in the PAIN by Kumar K in 2007. The most frequently occurring keywords were “spinal cord stimulation”, “neuropathic pain”, and “chronic pain”, etc. Conclusion The positive effect of SCS on pain treatment has continued to arouse the enthusiasm of researchers in this field. Future research should focus on the development of new technologies, innovative applications, and clinical trials for SCS. This study might facilitate researchers to comprehensively understand the overall perspective, research hotspots, and future development trends in this field, as well as seek collaboration with other researchers.